Data‐Driven Tuning Using Only One‐Shot Control Signal and Initial Controller Parameters. Issue 10 (19th July 2021) - Suzuki, Motoya; Ikezaki, Taichi; Kaneko, Osamu
Abstract : New parameter‐tuning methods, called data‐driven tuning, have been proposed, which can derive the controller parameters without using plant models. These include iterative feedback tuning (IFT), virtual reference feedback tuning (VRFT), and fictious reference iterative tuning (FRIT). In this study, a simple data‐driven tuning method is proposed. Through closed‐loop experiments, one‐shot input data and the initial controller parameters are obtained, based on which the control system is tuned. The tuned control system can realize a high tracking performance, and the desired response can be obtained. Furthermore, the validity of the proposed method is investigated through numerical simulation and experiments, which establish that the control performance is improved by the proposed parameter‐tuning method. The proposed method can obtain appropriate controller parameters. © 2021 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.